Analysis of Stress Factors and Coping in Primigravida Pregnant Women in Jakarta - Vivi Silawati; Afrizal; Nursyirwan Effendi; Masrul (Rajaki of Tulip Medika Publisher, 2025)
Pregnancy is ranked 12th out of 43 situations that can cause stress in pregnant women, especially primigravida pregnant women (Sarafino and Smith, 2014). Based on data from the 2018 Indonesian Health Profile, the number of pregnant women was 5,291,143 people, in DKI Jakarta in 2018 there were 187,291 people and in 2017 there were 222,298 people (Profil Kesehatan Indonesia, 2018). Based on preliminary results, primigravida pregnant women in Jakarta in 2017 experienced severe stress as much as 22% and moderate stress as much as 28%. Meanwhile, 17% of multigravida pregnant women experienced severe stress, and 30% experienced moderate stress. Based on the 1,522 respondents, 76.1% were mothers with a minimum age of 14 years and a maximum of 71 years (Aziz, 2020). Every pregnant woman has an effort to overcome or manage stress in her pregnancy to be able to adapt and overcome stress, the efforts made by pregnant women are called coping (Lazarus and Folkman, 1984). Coping is a way to adjust to stress or to overcome the conditions that follow, overcome, or evaluate when a response can no longer be used (Lazarus, 1976). Coping describes the process of cognitive activity accompanied by behavioral activity (Lazarus and Folkman, 1984). This study aims to explore and align indicators according to the research area carried out informally. This study uses an in-depth interview method using. In-depth interviews were conducted with 6 informants or primigravida pregnant women and 2 midwives to get input about the informants. The interview results were obtained as variable constructs and indicators that can build a model consisting of 8 variables and 3 indicators, namely coping variables, religious beliefs, personality, healthy lifestyles, perceptions, attitudes, social support, and self-empowerment.